ANALYSIS ON PROJECT PORTFOLIO MANAGEMENT PRACTICES IN INDIAN CONSTRUCTION INDUSTRY - Vinayagam, Sivasundara; R V, Hemprashant; S, Sruthy; Sanjeev, Vidya; Muralidhar, P (Journal of Civil Engineering, Science and Technology, 2021)
Project Portfolio management (PPM) is a combination of projects under the sponsorship of a particular construction organization sharing the scarce resources, managing projects and programs within the portfolio. It requires different strategies, models and practices. Many organizations across the country have projects in their sector in different places. However they abandoned temporarily suspended or closed within a decade which is troublesome. Proper PPM helps to execute the construction project effectively. As such, the aim of this research paper is to identify PPM practices in different construction organizations with a view to examine the effects of such practices on the project portfolio. The current research topic focuses on analysing the project performance of different construction projects using Project Portfolio Management practices. In this research a questionnaire survey related to the Project Portfolio Management on four major practices is carried out among the various professionals in Indian Construction Industry with help of Multi Criteria Decision Making (MCDM) techniques such as Entropy Method, SAW, CODAS methods and ranking the various project portfolio.